Neuronal ER-Signalosome Proteins as Early Biomarkers in Prodromal Alzheimer's Disease Independent of Amyloid-β Production and Tau Phosphorylation - Mesa-Herrera, Fátima; Marín, Raquel; Torrealba, Eduardo; Santos, Guido; Díaz, Mario (Frontiers in Molecular Neuroscience, 2022)
There exists considerable interest to unveil preclinical period and prodromal stages of Alzheimer’s disease (AD). Mild cognitive impairment (MCI) is characterized by significant memory and/or other cognitive domains impairments, and is often considered the prodromal phase of Alzheimer’s disease (AD). Cerebrospinal fluid (CSF) levels of β-amyloid (βA), total tau (t-tau) and phosphorylated tau (p-tau) have been used as biomarkers of AD albeit their significance as indicators during early stages of AD remains far from accurate. New biomarkers are being intensively sought as to allow identification of pathological processes underlying early stages of AD. Fifty three participants (75.4 ± 8.3 years) were classified in three groups as HC (cognitively normal healthy controls), MCI (mild cognitive impairment) and SMC (subjective memory complaints). Subjects completed different neurocognitive tests and underwent lumbar puncture for CSF extraction. CSF levels of ER-signalosome proteins, βA, t-tau p-tau, were submitted to univariate, bivariate and multivariate statistical analyses. We have found that components of the estrogen-receptor (ER)-signalosome, namely caveolin-1, flotilin-1, estrogen receptor alpha (ERα), insulin growth factor-1 receptor β (IGF1Rβ), prion protein (PrP) and plasmalemmal voltage dependent anion channel 1 (VDAC), could be detected in the CSF from all subjects of the HC, MCI and SMC groups. The six proteins appeared elevated in MCI and slightly increased in SMC subjects compared to HC, suggesting that signalosome proteins undergo very early modifications in nerve cells. Using a multivariate approach we have found that the combination of ERα, IGF-1Rβ, and VDAC are main determinants of group segregation with resolution enough to predict the MCI stage. Analyses of bivariate relationships indicated that colinearity of ER-signalosome proteins vary depending on the stage, with some pairs displaying opposed relationships between HC and MCI groups, and the SMC stage showing either no relationships or behaviors similar to either HC or MCI stages. Notably, most statistical analyses revealed no significant relationships or interactions with classical AD biomarkers at either disease stage. Finally, multivariate functions were highly correlated with outcomes from neurocognitive tests for episodic memory. These results demonstrate that alterations in ER-signalosome might provide useful diagnostic information on preclinical stages of AD, independently from classical biomarkers.